Characterization and measurement of CD5+ B cells in normal and Trypanosoma congolense- infected cattle - Naessens, Jan; Williams, D.J.L. (Wiley, 1992)
CD5+ B cells in cattle are present in peripheral blood and spleen, but not in lymph nodes, tonsils or Peyer's patches. Compared to classical B cells, they express similar levels of B cell surface markers, but have higher levels of surface IgM. We failed to find evidence for IgD on bovine B lymphocytes. The CD5+ B cells expressed CD11b (Mac‐1). Another small subpopulation of B cells carried CD11b but not CD5. In cattle infected with Trypanosoma congolense, a dramatic increase in the percentage of CD5+ B cells in blood and spleen was observed. This increase occurred 7‐10 days after parasites were first detected in the blood and correlated with the increase in serum IgM and the increase in the absolute number of B cells that is typical to trypanosome‐infected animals. The increase in B cells was found to be due mainly to the expansion of the CD5+ B cell subpopulation. The cause of the amplification of the CD5+ B cells and their possible involvement in the production of autoantibodies and non‐parasite‐specific antibodies which have been described in trypanosome‐infected animals are discussed.